Optimasi Metode Kerja Bore Pile Pada Proyek Taman Teknologi Tower Turyapada Oleh PT XYZ Dengan Pendekatan Six Sigma DMAIC - Sufi, Dhamar Buana; I Gusti Ngurah Priambadi; Ni Luh Putu Lilis Sinta Setiawati (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This research aims to optimize the bore pile work method on the Turyapada Tower Technology Park project by PT XYZ using the Six Sigma DMAIC approach. At the define stage, the identified problem was the discrepancy between actual and theoretical bore pile volumes, impacting cost, time, and quality. During the measure stage, the defect rate was 134,000 per million opportunities, equating to 2.61 sigma. Analysis using a fishbone diagram revealed several factors causing the problem: short casing installed post-drilling, uncoated bore pile walls, and inappropriate drill bits that slowed work in red soil terrain containing hard rock. Proposed improvements in the improve stage include using full casing or longer casing to reduce the risk of wall collapse, drilling and installing casing simultaneously, coating bore pile walls with bentonite to make them smoother and straighter, and using a combination of DTH and Tricone drill bits to expedite work. At the control stage, the 5W+1H method is used to ensure each improvement is implemented effectively and sustainably. Implementing these solutions is expected to enhance the effectiveness, efficiency, and quality of bore pile work, as well as reduce the volume discrepancy between actual and theoretical measures.